Munakahat dan Fulfillment of Family Livelihood: A Normative Analysis of Islamic Law - Novi Yanti; Eki Candra; Irwan Tutrisno; Nazwa Yunissa Utami; Wulan Dari (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
This study is motivated by the importance of munakahat in Islamic jurisprudence as a normative framework governing marital relationships, particularly regarding the obligation of family maintenance (nafaqah). In contemporary social contexts, economic dynamics and shifting family roles have raised various challenges in understanding and implementing this obligation. Therefore, this research aims to analyze the concept of munakahat and the fulfillment of family maintenance from the perspective of normative Islamic jurisprudence. This study employs a qualitative method with a normative doctrinal approach through library research. Primary data sources include the Qur’an, hadith, and classical fiqh texts, while secondary sources consist of books and contemporary scholarly journal articles. Data analysis is conducted using content analysis and comparative examination of juristic opinions. The findings indicate that the obligation of maintenance is a legal consequence of the marriage contract, carrying both moral and legal responsibility. Islamic jurisprudence on munākahāt also demonstrates flexibility in determining maintenance standards based on the husband’s capacity and socio cultural context (‘urf). In conclusion, the concept of maintenance within munakahat functions not merely as a legal obligation but as a mechanism for ensuring justice and strengthening Muslim family resilience.